Microstructure refinement for high modulus in-situ metal matrix composite steels via controlled solidification of the system Fe–TiB2. (1st September 2015) - Springer, H.; Aparicio Fernandez, R.; Duarte, M.J.; Kostka, A.; Raabe, D.
Abstract: Microstructures of Fe–TiB2 metal-matrix-composites formed in-situ from Fe–Ti–B melts were investigated for hypo- and hyper-eutectic concentrations down to atomic-scale resolution. Special emphasis is laid on the influence of the solidification rate on particle size, morphology and distribution as well as their relation to mechanical properties. Innovative routes for the cost-effective production of stiff and ductile high modulus steels for lightweight structural applications are discussed, focusing on hyper-eutectic compositions due to their high stiffness/density ratio: firstly, very slow cooling allows the primary particles floating to the top of the cast, from which they can either be easily removed for retaining bulk material containing only fine-dispersed eutectic particles, or be kept and utilised as a wear resistant surface. Secondly, annealing of amorphous matrix material obtained from very fast solidification leads to fine dispersed nano-scaled precipitation of TiB2 particles.